2002
DOI: 10.1074/jbc.m200453200
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Specificity JKAP Specifically Activates the c-Jun N-terminal Kinase Pathway

Abstract: MAPKs are activated by a wide range of diverse stimuli and are essential for various cellular processes, such as stress responses, apoptosis, proliferation, differentiation, and early embryonic development (1-3). The prototypical MAPK signaling cascade is a three-kinase module, consisting of MAP kinase kinase kinase (MAP3K), MAP kinase kinase (MAP2K), and MAPK (1, 2, 4). The upstream molecules that link the MAPK module to extracellular stimuli include small G proteins and a group of mammalian Ste20-like kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
109
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 50 publications
3
109
1
Order By: Relevance
“…VHX associates with p38 and Jnk in vivo but not in vitro (30,47), suggesting that the interaction requires additional components. Candidates include MKK7 or c-Jun, both of which interact with VHX (31,47). Together, these results indicate that VHX may play a regulatory role in the Jnk or p38 pathways, but they do not yet reveal what phosphoprotein(s) VHX dephosphorylates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VHX associates with p38 and Jnk in vivo but not in vitro (30,47), suggesting that the interaction requires additional components. Candidates include MKK7 or c-Jun, both of which interact with VHX (31,47). Together, these results indicate that VHX may play a regulatory role in the Jnk or p38 pathways, but they do not yet reveal what phosphoprotein(s) VHX dephosphorylates.…”
Section: Discussionmentioning
confidence: 99%
“…SKRP1 is involved in the regulation of Jnk and interacts with its upstream regulators MKK7 and ASK1 (apoptosis signal-regulating kinase 1) but not with MEKK1 (44,45). Finally, VHX also has been linked to MAP kinase regulation, with a proposed role as a positive regulator of Jnk activation (31,47). VHX associates with p38 and Jnk in vivo but not in vitro (30,47), suggesting that the interaction requires additional components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, we also cloned a new class of DSPs (LMW-DSP1, -DSP2, -DSP4, -DSP6, -DSP10 and -DSP11) from a mouse testis cDNA library and found that they were specifically and abundantly expressed in the testes Aoki et al, 2001). Recently, LMW-DSP2 was found to belong to the subfamily of small DSPs related to the Vaccinia virus VH1 phosphatase (Guan et al, 1991;Aoyama et al, 2001;Shen et al, 2001;Alonso et al, 2002;Chen et al, 2002). The finding that VH1 phosphatase blocked Figure 1 LIF and IL-6 induced mRNA expression of LMW-DSP2 in testicular and hepatoma cells.…”
mentioning
confidence: 95%
“…LMW-DSP2 was found to dephosphorylate and deactivate p38 MAPK and JNK, but not ERK . LMW-DSP2 has also been referred to as VHX (Alonso et al, 2002), JSP1 (Shen et al, 2001) and JKAP (Chen et al, 2002). However, the physiological functions of LMW-DSPs have remained unclear, since they appear to be less efficient than many other MAPK-specific DSPs.…”
mentioning
confidence: 99%